2011
DOI: 10.1155/2011/237932
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Weight Control Strategies and Their Effects on the Regulation of Hormonal Balance

Abstract: The estimated prevalence of obesity in the USA is 72.5 million adults with costs attributed to obesity more than 147 billion dollars per year. Though caloric restriction has been used extensively in weight control studies, short-term success has been difficult to achieve, with long-term success of weight control being even more elusive. Therefore, novel approaches are needed to control the rates of obesity that are occurring globally. The purpose of this paper is to provide a synopsis of how exercise, sleep, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 172 publications
(267 reference statements)
1
22
0
6
Order By: Relevance
“…Epidemiological research shows more frequent meal intakes are associated with lower fasting blood glucose and insulin, cholesterol and triglycerides, and a reduced risk of developing type 2 diabetes and coronary heart disease [12,68]. Acute intervention studies have partially supported these findings ( Table 1), showing that division of a meal into smaller portions reduces the insulin excursion in response to each meal and overall [38,43,69], although one study did not detect a difference in the overall insulin AUC [43].…”
Section: Does Increased Meal Frequency Improve Glycaemic Control and mentioning
confidence: 99%
“…Epidemiological research shows more frequent meal intakes are associated with lower fasting blood glucose and insulin, cholesterol and triglycerides, and a reduced risk of developing type 2 diabetes and coronary heart disease [12,68]. Acute intervention studies have partially supported these findings ( Table 1), showing that division of a meal into smaller portions reduces the insulin excursion in response to each meal and overall [38,43,69], although one study did not detect a difference in the overall insulin AUC [43].…”
Section: Does Increased Meal Frequency Improve Glycaemic Control and mentioning
confidence: 99%
“…Most of them found that having three or fewer meals/day is associated with excessive abdominal fat, when compared with having more than three meals/day; however, this association can only be seen among men [64][65][66][67]. In general, increased eating frequency has been postulated to increase metabolism [69], appetite control, and food intake and to improve glucose and insulin control [70][71][72]. However, this association only among men could be due to the fact that men who have a high eating frequency also have a healthier lifestyle, including the practice of physical activity and healthier eating habits, which results in reduced body fat and WC [73].…”
Section: Eating Frequencymentioning
confidence: 99%
“…Most studies on the relationship between food intake-regulating hormones and diet have focused on understanding the underlying mechanisms involved in obesity and its related disorders in humans (Schwarz et al, 2011). In this study, the strongest correlation was found between the concentration of acyl-ghrelin and cortisol in both pregnant and lactating sows at 0 min.…”
Section: Discussionmentioning
confidence: 47%